STUDENT READING BOOK SELECTION FOR PROFESSIONAL PURPOSES (NEEDS ANALYSIS STUDY) - Lilik Purwaningsih (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the choice of student reading books that are directed to support their professional goals. A descriptive qualitative approach is used to explore preferences, motivations, and factors that influence students in choosing reading. Data was collected through in-depth interviews, observations, and document review on students from various study programs. The results show that the majority of students choose books that are relevant to the field of work they want to pursue, such as practical management, education, and applied technology. The dominant factors that affect the selection are the relevance of the content to career, lecturer recommendations, and the availability of books in the library. However, a gap was found between the needs of students and the available reading collection, especially in the current and applicative aspects. Students also develop independent strategies in finding alternative reading sources digitally. These findings confirm the importance of information literacy and the support of educational institutions in providing professional reading according to their needs. This study recommends strengthening the professional literacy ecosystem through improving library collections, digital literacy training, and recognition of students' independent learning.